MICROWAVE ASSISTED EXTRACTION; PHYTOCHEMICAL EVALUATION OF MALAYSIAN PALM OIL TRUNK EPIPHYTES FERNS - Kormin, Faridah; Khan, Muhammad; Iwansyah, Ade Chandra (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The objective of this research was to evaluate the, total phenolic contents (TPC), total flavonoid contents (TFC), antioxidant activity, cytotoxicity and functional group of epiphytes ferns grows on the Malaysian palm oil trunk (MPOTEF): that includes Nephrolepis biserrata (NBF), Davallia denticulata (DDF), Asplenium longissimum (ALF), Gonioplebium percussum (GPF), Stenochlaena palustris (SPF), Vittaria elongata (VLF) and Vittaria ensiformis (VSF). Methods: For extraction, microwave oven assisted method was used. TPC was determined by following the Folin-Ciocalteu colorimetric method and TFC was determined using aluminium chloride colorimetric assay. Antioxidant activity was determined by DPPH-scavenging assay methods. Results: All the ferns exhibited good results of TPC, TFC and antioxidant activity. SPF showed highest TPC and TFC in aqueous extracts; 639.4 mg/g and 172.71 mg/g respectively, and the same result showed in ethanol extracts; 271.61 mg/g and 174.54 mg/g, respectively. SPF also giving scavenged the free radicals 94.85% in aqueous extract while 98.17% in ethanol extract. The brine shrimp cytotoxicity revealed DDF having the strongest result (130Âµg/ml (dry mass) in ethanol extract as compared to in water extract and other species. The FTIR indicated the presence of alcohols, phenols, amine, alkanes, alkenes, alkyl halides, carbonyl, nitro compounds, acid, ether and ester in different species and extracts. Prediction Activity Spectra of Substances (PASS) program for SPF extract showed the most probable activities are antioxidant, lipid peroxidase inhibitor and radical scavengers. Conclusion: All the ferns showed active toxicity in ethanol extract whereas inactive in the water extracts except SPF. Amongst them, SPF shows its capability as a natural antioxidant source appears to be an alternative to synthetic antioxidants. It can be seen from the results of PASS for SPF extract that most probable activities are antioxidant, lipid peroxidase inhibitor and radical scavengers supported by cytotoxicity and FTIR results. Thus, the present approach can be very useful in fern prediction activity according to their required properties. Keywords: Epiphytes fern, Palm oil, Total phenolic compound, Total flavonoid compound, Antioxidant activity, Brine shrimp lethality test, FTIR Â 